Resolution of Diastereomeric Tartaric Acid Monoamides by Reversed-phase High Performance Liquid Chromatography - Munegumi, T.; Inaba, K.; Kikuchi, K.; Tauchi, Y.; Harada, K. (Asian Journal of Chemistry, 2010)
Diastereomer resolution by high performance liquid chromatography (HPLC) has been useful for determining the correlation between molecular structure and hydrophobicity. Three pairs of diastereomeric tartaric acid monoamides (O,O'-diacetyl-(2R, 3R)-tartaric amides) are resolved into each diastereomer by achiral reversed-phase HPLC (RP-HPLC). There are some correlations between the molecular structure and the elution order of the diastereomers. O,O'-Diacetyl- (2R,3R)-tartaric acid (R)-amides ((R,R,R)-tartaramides) are eluted faster than (R,R,S)-tartaramides. 1H NMR spectra of these compounds in acetonitrile-d3 (CD3CN) shows that the dihedral angle is about 110º around the vicinal protons of the tartaric acid moiety. When we adopt this value for calculation of the molecular structure, the logarithm of the partition coefficient (log P value) of tartaramides in n-octanol per water explains the elution order of diastereomers. The findings play a role in both determination of the elution order and the conformation of similar chiral compounds in RP-HPLC.